Molecular Characterization of Voltage-Gated Sodium Channels and Their Relations with Paralytic Shellfish Toxin Bioaccumulation in the Pacific Oyster Crassostrea gigas - Boullot, Floriane; Castrec, Justine; Bidault, Adeline; Dantas, Natanael; Payton, Laura; Perrigault, Mickael; Tran, Damien; Amzil, Zouher; Boudry, Pierre; Soudant, Philippe; Hegaret, Helene; Fabioux, Caroline (Marine Drugs, 2017)
Paralytic shellfish toxins (PST) bind to voltage-gated sodium channels (Nav) and block conduction of action potential in excitable cells. This study aimed to (i) characterize Nav sequences in Crassostrea gigas and (ii) investigate a putative relation between Nav and PST-bioaccumulation in oysters. The phylogenetic analysis highlighted two types of Nav in C. gigas: a Nav1 (CgNav1) and a Nav2 (CgNav2) with sequence properties of sodium-selective and sodium/calcium-selective channels, respectively. Three alternative splice transcripts of CgNav1 named A, B and C, were characterized. The expression of CgNav1, analyzed by in situ hybridization, is specific to nervous cells and to structures corresponding to neuromuscular junctions. Real-time PCR analyses showed a strong expression of CgNav1A in the striated muscle while CgNav1B is mainly expressed in visceral ganglia. CgNav1C expression is ubiquitous. The PST binding site (domain II) of CgNav1 variants possess an amino acid Q that could potentially confer a partial saxitoxin (STX)-resistance to the channel. The CgNav1 genotype or alternative splicing would not be the key point determining PST bioaccumulation level in oysters.